PEMBERIAN MASASE DENGAN PERKEMBANGAN USIA 12-24 BULAN DI POSYANDU RT 09 RW 06 KELURAHAN BANYU URIP KECAMATAN SAWAHAN SURABAYA - Siti Nurjanah (Jurnal Ilmiah Kesehatan, 2016)
the relation in giving massage with the growth of children in age 12-24 months. Children are normally able to walk in age 14 months. However, occasionally some of them could not walk due the massage that is given to them is not appropriate with their age. Based on the study purposed by Purwati in 2010, she found 27 of children under five years, 12 out of them have an indecisive growth, 2 out of them have divergent growth, and 13 out of them have appropriate growth. This present study purposes to get the understanding of the relation in giving massage with the growth of children in age 12-24 months. The researcher gets the sample in Posyandu RT 09 RW 06 Kelurahan Banyu Urip Kecamatan Sawahan Surabaya. The approach of this study is analysis by cross sectional approach. The population of this study is 45 mothers and their 12-24 months children with the sample is 41 respondents taken by simple random sampling, variable of this study is giving massage and children development with questionnaire instrument and KPSP. The researcher uses statistical test from Rank Spearman with the significant 0.05. The result of this study shows that almost a half of children in age 12-24 months (39.1%) have good massage and (36.6%) children get an appropriate growth. The result of statistical test of Rank Spearman shows that (0.00) < (0.05), therefore Ho is ignorance. It means that there is a relation in giving massage with the growth of children in age 12-24 months. Conclusion from this study is the better massage provided the better the child's developmental level. The researcher suggests the mother to be more active in children give massage and find the information about the stimulation of children development, thus, the parents are able to give the appropriate stimulation for their children.